2015
DOI: 10.5455/jmp.20151111030040
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and vitamin C analysis of wild edible plants consumed by Bodos of Assam, India

Abstract: Aim: The State of Assam is gifted with diverse flora including thousands of wild edible plants. The consumption of a large variety of wild plants by Bodos, an ethnic group and dominant inhabitant of Bodoland Territorial Area Districts of Assam of NorthEast India, is a common practice since time immemorial. The objective of this study was to investigate the nutritional values of wild edible plants consumed by the Bodos of this region. Materials and Methods: In this study, twelve wild edible plants viz. Blumea l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 11 publications
9
26
0
Order By: Relevance
“…Similarly, MeEf showed higher protein content (310.40±11.44 µg/mg extract) among all the tested plants. Recent studies by Swargiary et al [30] and Narzary et al [31] also revealed a similar range of carbohydrate and protein content in the wild edible plants. Quantitative study of TPC showed highest concentration in MeEf (245.66±9.68 µg/mg extract) followed by MeAc (122.41±8.58 µg/mg extract), MeHr (116.40±3.53 µg/mg extract) and MeCd (63.60±5.77 µg/mg extract), respectively.…”
Section: Phytochemical Analysismentioning
confidence: 72%
“…Similarly, MeEf showed higher protein content (310.40±11.44 µg/mg extract) among all the tested plants. Recent studies by Swargiary et al [30] and Narzary et al [31] also revealed a similar range of carbohydrate and protein content in the wild edible plants. Quantitative study of TPC showed highest concentration in MeEf (245.66±9.68 µg/mg extract) followed by MeAc (122.41±8.58 µg/mg extract), MeHr (116.40±3.53 µg/mg extract) and MeCd (63.60±5.77 µg/mg extract), respectively.…”
Section: Phytochemical Analysismentioning
confidence: 72%
“…Leaves and twigs of Lippia javanica are used as food additives in Kenya [6] and leafy vegetable in India [12, 13]. Lippia javanica is popular as herbal tea, particularly in Botswana, South Africa, and Zimbabwe [711].…”
Section: Traditional Uses Of Lippia Javanicamentioning
confidence: 99%
“…Multiple classes of phytochemicals including volatile and nonvolatile secondary metabolites, such as alkaloids, amino acids, flavonoids, iridoids, and triterpenes as well as several minerals, have been identified from L. javanica [15, 7, 13, 27, 73, 78, 81, 8386, 88–94, 120, 123, 125127]. Leaves, flowers, and twigs of L. javanica have a wide variety of the so-called classic nutrients, such as minerals, carbohydrates, proteins, fats, and vitamins (Table 2).…”
Section: Phytochemical Constituents and Nutritional Composition Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The key nutrients of life are proteins, fats and carbohydrates. The food rich in proteins, fats and carbohydrates supplies more energy which is responsible for doing various activities in our daily life [12,26].…”
Section: Resultsmentioning
confidence: 99%